Method of consumption in spare parts for machine repair - Dashyvets, Halyna; Дашивець, Галина Іванівна; Komar, Artem; Комар, Артем Станіславович (Запоріжжя: ТДАТУ, 2025)
The system of material and technical support for the machine and tractor fleet has a significant impact on its operational readiness. The efficiency of machinery operation can be enhanced through the development of new methods or the improvement of existing approaches for forecasting the required quantity of spare parts, which represent temporarily unused economic resources. Inventory levels must not exceed established norms, and spare parts should not remain in storage for extended periods without utilization, in order to avoid immobilization of the enterprise’s working capital. Conversely, excessive reduction of spare part inventories poses the risk of increased costs associated with prolonged downtime due to the absence of necessary components for repair. Therefore, determining the optimal quantity and nomenclature of spare parts is one of the priority tasks in managing operating costs and improving the technical readiness of machinery.
Keywords: machine repair; system of material and technical support